Aplikasi Metode Min-Max di PT. T dalam Merencanakan Kebutuhan Persediaan Bahan Baku pada Proses Body Repair Mobil - Rudi Darmawan; Susanti Sundari; Burhan Nudin (Industrika : Jurnal Ilmiah Teknik Industri, 2023)
Research on planning spare part inventory in the Car Body Repair Process at PT. T, which is a company in the automotive sector, uses the Min-Max method which aims to be able to better plan spare part inventory for customer satisfaction. This was motivated by the fact that the spare parts needed were not available, causing the car repair process to be delayed and cars having to stay overnight while waiting for the parts to be ordered and to arrive. From the results of data processing using the min-max method which has been carried out, it was concluded that the more often spare parts are used, the greater the minimum and maximum values when compared to spare parts that are rarely used. That there are 6 items out of 61 spare parts (0.1%) that are recommended not to have minimum stock or do not need stock because there has been no demand for parts for quite a long time. Meanwhile, for other items, it is recommended to stock at least 1 to meet existing demand. Apart from that, there are 5 items or 0.1% of spare parts with a maximum stock of only one because there is still demand, and 27 items out of 61 spare parts (44%) are recommended to have more than 10 maximum stocks. Keywords: Inventory, Min-Max Stock, Spare part